1999
DOI: 10.1016/s0885-3924(99)00078-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Recognition of the Symptoms Experienced by HIV Patients

Abstract: To assess how well physicians recognize common symptoms in HIV patients and identify factors associated with symptom recognition, a multicenter cross-sectional survey was performed in a random sample of 118 hospitalized and 172 ambulatory HIV patients, and their attending physicians. Patients' reports of 16 different symptoms were compared to physicians' reports of whether each symptom was present and/or specific treatments prescribed. Overall, fatigue, anxiety, skin problems, fever, and weight loss were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 27 publications
(24 reference statements)
2
26
0
Order By: Relevance
“…All records for changes in body shape are removed for chronicity; the questionnaire did not distinguish between loss and gain events and whether they had separate onsets. individuals [14][15][16] and in other patient populations. 9,17 A 20-item self-completed HIV symptom index has been developed in an effort to standardize reporting and improve completeness of symptom documentation.…”
Section: Discussionmentioning
confidence: 99%
“…All records for changes in body shape are removed for chronicity; the questionnaire did not distinguish between loss and gain events and whether they had separate onsets. individuals [14][15][16] and in other patient populations. 9,17 A 20-item self-completed HIV symptom index has been developed in an effort to standardize reporting and improve completeness of symptom documentation.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Symptom research has looked at patient-clinician agreement of symptoms related to angina pectoris, 23 myocardial infarction, 24,25 psychological and somatic disorders, 8,[26][27][28][29] HIV infection, 30 and cancer. 31,32 One study found fair to substantial agreement between adult selfassessment and clinician assessment on the symptoms related to 'strep throat'.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is the most frequent and debilitating complaint of HIV-positive people, with prevalence rates of up to 98% in studies of seropositive individuals (e.g., Anandan, Braveman, Kielhofner, & Forsyth, 2006;Breitbart, McDonald, Rosenfeld, Monkman, & Passik, 1998;Coleman et al, 2006;Duran et al, 2001;Fontaine, Larue, & Lassauniere, 1999;Henderson, Safa, Easterbrook, & Hotopf, 2005;Molassiotis, Callaghan, Twinn, & Lam, 2001;Norval, 2004;Simmonds, Novy, & Sandoval, 2005;Sullivan, Dworkin, & the Adult and Adolescent Spectrum of HIV Disease Investigators, 2003;Vogl et al, 1999;Voss, 2002Voss, , 2005. The consequences of fatigue include having to stop working, limiting one's involvement with family and friends, being unable to manage one's finances, and needing an entire day to get through the simplest of household chores (Anandan et al, 2006;Barroso, 2001;Jenkin, Koch, & Kralik, 2006).…”
Section: Introductionmentioning
confidence: 99%